Seronegative autoimmune hepatitis – A case report - Bharati, Hemant; Hittanagi, Poonam; Patil, Mohan Anantrao; Kurane, Anil Bapurao; Karanam, Anushna (Indian Journal of Child Health, 2019)
Autoimmune hepatitis (AIH) is a complex liver disease. It is reported in children and adults of all age groups. An 11-year-old male child was admitted in our hospital for anorexia and yellowish discoloration of eyes, skin, and urine for 2 months. He had fever, itching was passing pale-colored stools. The child had hepatosplenomegaly and viral hepatitis markers as well as autoimmune markers were negative. Liver biopsy was suggestive of AIH. The child was started on prednisolone and showed drastic improvement clinically as well as biochemically. This was a case of seronegative AIH, which responded very well to corticosteroids. Hence, high index of suspicion is required to diagnose the case of seronegative AIH.